Effect of Spirulina addition on the physicochemical and structural properties of extruded snacks - Bárbara Franco LUCAS (Ciência e Tecnologia de Alimentos, 2017)
Nowadays the demand for practical food like snacks increases worldwide, however the nutritional value in most these formulations is reduced. Due to its chemical composition with high protein concentration, the microalga Spirulina has been used on the production of enriched foods. The present study aimed to evaluate the effects of Spirulina sp. LEB 18 addition on snacks formulations and extrusion conditions on the physicochemical and structural properties of snacks. Protein concentration and physical properties such as expansion index, bulk density, hardness, water absorption index, water solubility index and color were determined. The results showed that the addition of Spirulina sp. LEB 18, temperature in the last zone of the extruder and feed moisture influenced the product responses. The increase in feed moisture increased the hardness, bulk density and water absorption index of the snacks. Higher concentrations of microalga produced snacks with higher protein content, total color difference (ΔE) and compact structure. The addition of 2.6% Spirulina produced snacks with up to 11.3% protein and with adequate physical and structural properties for consumption. Thus, snacks containing Spirulina are an alternative to the demand for healthy food of practical consumption.